Assessing readiness factors for implementation of LGBTQ+ affirmative primary care initiatives: Practice implications from a mixed-method study - Willging, Cathleen E.; Sklar, Marisa; Eckstrand, Kristen; Sturm, Robert; Davies, Sonnie; Kano, Miria (Frontiers in Health Services, 2022)
Introduction: Access and utilization barriers in primary care clinics contribute to health disparities that disproportionately affect lesbian, gay, bisexual, transgender, and queer (LGBTQ+) people. Implementing inclusive practice guidelines in these settings may decrease disparities. The purpose of this exploratory/developmental study is to identify key issues affecting the readiness of primary care clinics to implement such guidelines. Methods: Using a concurrent mixed-method research design, we conducted surveys, interviews, and focus groups with 36 primary care personnel in clinics in New Mexico, USA, to examine readiness to implement LGBTQ inclusive guidelines, analyzing factors affecting motivation, general organizational capacities, and innovation-specific capacity. We supplemented these data by documenting LGBTQ+ inclusive policies and practices at each clinic. We undertook descriptive analyses and between-subscale comparisons controlling for within-rater agreement of the survey data and iterative coding and thematic analysis of the qualitative data. Results Quantitatively, participants reported significantly more openness towards adopting guidelines and attitudinal awareness for developing LGBTQ+ clinical skills than clinical preparedness, basic knowledge, and resources to facilitate implementation. Six themes derived from the qualitative findings corroborate and expand on these results: (1) treating all patients the same; (2) addressing diversity in and across LGBTQ+ populations; (3) clinic climates; (4) patient access concerns; (5) insufficient implementation support; and (6) leadership considerations. Conclusion This study demonstrates that personnel in primary care clinics support initiatives to enhance service environments, policies, and practices for LGBTQ+ patients. However, drawing on Iris Young’s theory of structural injustice, we found that neutralizing discourses that construct all patients as the same and time/resource constraints may diminish motivation and capacity in busy, understaffed clinics serving a diverse clientele and reinforce inequities in primary care for LGBTQ+ people. Efforts are needed to build general and innovation-specific capacities for LGBTQ+ initiatives. Such efforts should leverage implementation teams, organizational assessments, education, leadership support, community engagement, and top-down incentives.